Olive Cellulosic Fibre Based Epoxy Composites: Thermal and Dynamic Mechanical Properties. Issue 15 (23rd November 2022) - Jawaid, M.; Awad, S.; Fouad, Hassan; Alothman, Othman Y.; Saba, N.; Sain, M.; Leao, A. L.
ABSTRACT: This study deals with the evaluation of the impact of three different olive tree residues: olive tree small branch (OTS), olive tree big brunch (OTB) and olive tree leaves (OTL) as a filler on thermal properties of olive/epoxy biocomposites. Olive residue-based epoxy composites were processed at 40% filler loading to fabricate biocomposites by hand lay-up techniques. The thermal stability was investigated by thermal gravimetric analysis (TGA) while dynamic mechanical properties and thermal expansion of fiber composites were analyzed by the dynamic mechanical analyzer (DMA) and thermomechanical analyzer (TMA). The OTL/epoxy composite showed improvement in thermal and DMA (storage modulus, loss modulus, and damping factor) as compared to OTB and OTS/epoxy composites. On the other hand, OTS filled epoxy matrix exhibited the greatest thermal degradation temperature while CTE was the lowest and greatest dynamic mechanical properties over all composites. DMA results revealed that the OTS/epoxy composite possesses the highest storage modulus in view of the strong fiber/matrix interfacial. It is evident from obtained results that the incorporation of olive biomass enhanced thermal, dimensional, and dynamic mechanical characterizations of epoxy composites and appropriate use for automotive or materials applications of building that mandate high-dimensional stability and dynamic mechanical characterizations.